Spotting the differences between active and non-active twin galaxies on kpc-scales: a pilot study. Issue 3 (8th March 2019) - del Moral-Castro, I; García-Lorenzo, B; Ramos Almeida, C; Ruiz-Lara, T; Falcón-Barroso, J; Sánchez, S F; Sánchez-Blázquez, P; Márquez, I; Masegosa, J
ABSTRACT: We present a pilot study aimed to identify large-scale galaxy properties that could play a role in activating a quiescent nucleus. To do so, we compare the properties of two isolated nearby active galaxies and their non-active twins selected from the Calar Alto Legacy Integral Field Area (CALIFA) survey. This pilot sample includes two barred and two unbarred galaxies. We characterize the stellar and ionized gas kinematics and also their stellar content. We obtain simple kinematic models by fitting the full stellar and ionized gas velocity fields and just the approaching or receding sides. We find that the analysed active galaxies present lopsided discs and higher values of the global stellar angular momentum (λ R ) than their non-active twins. This could be indicating that the stellar discs of the AGN gained angular momentum from the inflowing gas that triggered the nuclear activity. The inflow of gas could have been produced by a twisted disc instability in the case of the unbarred AGN, and by the bar in the case of the barred AGN. In addition, we find that the central regions of the studied active galaxies show older stellar populations than their non-active twins. The next step is to statistically explore these galaxy properties in a larger sample of twin galaxies.